Construction of women's roles in the Andingingi Ritual in the Ammatoa Customary Area, Tana Toa Village, Kajang District, Bulukumba Regency - Nurfadillah, Nurfadillah; Radjab, Mansyur; RAF, Nuvida; Sabiq, Muhammad (Sangia Research Media and Publishing, 2023)
Gender equality constructed through the culture of the Kajang Tribe in Bulukumba is very interesting to watch because, generally, in other societies it is hierarchical (patriarchal). Culture provides a large space for women's involvement in the Andingingi Ritual. The implementation is always coupled with the Bulukumba cultural festival which is attended by various groups and tourists. This study aims to determine the process of externalization, objectification and internalization of women in the Andingingi Ritual. This research was carried out using a qualitative approach with the case study method. Data collection was carried out using observation, interviews, and documentation techniques. Data analysis techniques are carried out by reducing data, presenting data and drawing conclusions. The research informants consisted of traditional leaders (Ammatoa), traditional stakeholders (Galla), the Kajang community and the village government. The results of this study indicate that the externalization of women's roles in the Andingingi ritual process, including A'runding (ritual preparation meetings), Appalenteng Ere (moving holy water to the ritual location), Drinking Tuak (drinking blessings), Abbebese (sprinking holy water around the four corners cardinal points), Bacca Or Mabarra' (gluing Bacca to the forehead and neck), Allabiang Dedde (gathering all the produce of the garden to be blessed by Ammatoa) and giving pap Pasang. Its objectivity can be seen from the habits that have been institutionalised by society. Women are starting to pay attention to feedback from the activities they carry out based on the results of their social interactions, for example the role played by women during ritual preparation to completion. Although internalisation can be seen from the acceptance of social values contained in each ritual activity, including the value of Gotong Royong, Mutual help, Solidarity, and Communicative values.